2018
DOI: 10.4025/jphyseduc.v29i1.2942
|View full text |Cite
|
Sign up to set email alerts
|

O Efeito Da Idade Relativa No Voleibol Brasileiro De Elite

Abstract: RESUMOO efeito da idade relativa (EIR) refere-se à vantagem de atletas nascidos nos primeiros meses do período de seleção em relação a seus pares nascidos em meses posteriores no processo de seleção esportivo, que tende a favorecer atletas que encontram-se em estágio maturacional ou de desenvolvimento físico mais avançados que o de seus colegas mais jovens nascidos no mesmo ano. Esse favorecimento ocorre principalmente em esportes cuja característica física é determinante para se obter sucesso, como o voleibol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 30 publications
(59 reference statements)
2
10
0
1
Order By: Relevance
“…Our finding of no RAE among female Superliga A athletes aligned with Castro et al 2022a, andParma andPenna's (2018). Thus, our data add to earlier evidence that RAE magnitude may decrease or even revert in some specific elite sport contexts (de la Rubia et al, 2020;Gibbs et al, 2012).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our finding of no RAE among female Superliga A athletes aligned with Castro et al 2022a, andParma andPenna's (2018). Thus, our data add to earlier evidence that RAE magnitude may decrease or even revert in some specific elite sport contexts (de la Rubia et al, 2020;Gibbs et al, 2012).…”
Section: Discussionsupporting
confidence: 85%
“…Considering the multifactorial and context-specific nature of RAE, factors such as the athletes' sex and competitive level within a sport may affect the likelihood of RAE occurrence (Castro et al, 2022b;Castro, Francisco, et al, 2022;Figueiredo et al, 2022;Smith et al, 2018;Wattie et al, 2015). Regarding sex differences, previous research found that RAE occurs to a smaller extent in women's than in men's sports (de la Rubia et al, 2020;Lidor et al, 2021;Parma & Penna, 2018). This may be due in part to young female athletes' tendencies to achieve their individual peak growth spurt earlier than boys (Malina et al, 2015), perhaps meaning that, by the point of sport selection, prospective female athletes are comparable in their maturation, giving coaches less basis for discriminating between them in the selection process and reducing the RAE occurrence when later measured among elite players (Castro et al, 2022a;Castro, Aguiar, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O EIR está presente nas mais diferentes modalidades esportivas, tanto nos esportes coletivos, como futebol(5,6) e voleibol (7), quanto nos individuais como tênis (8), triatlo (9), lutas(10,11) e natação (12), contudo apresenta maior magnitude nos esportes individuais (13). Ao se considerar atletas nascidos nos meses iniciais, os mesmos podem apresentar melhor rendimento esportivo se comparados a atletas nascidos nos meses finais do mesmo ano (14,15) 22,9±3,4 anos de idade), considerando em sua análise o sexo, tipos de provas e excelência esportiva.…”
Section: Introductionunclassified
“…In the past two decades, it has been identified that athletes who are born early (first or second trimester) in competition year have been overrepresented in elite teams in young and senior age brackets (for a review, see 1,2 ). The possible advantaged presented by those early born athletes has been frequently called the relative age effect (RAE), and this effect is observable in team sports like basketball 3 , soccer 4 , rugby 5 , volleyball 6 , and in induvial sports like tennis 7 , track and field 8 and Judo 9 and in different levels ranging from young amateurs 10 to super-elite athletes 11 .…”
Section: Introductionmentioning
confidence: 99%